Malay reservation : a Malay dilemma / Haliza Aini Othman - Haliza Aini, Othman (Faculty of Law, 1986)
The basic aim of the Malay Reservation Enactment was the perpetuation of the ownership of lands under Malay settlement and cultivation in the hands of the Malays and hence the preservation of the social, economic and physical intergrity of the Malay peasantry. However the role of the Malay Reservations in the overall protection of Malay interest in rural and urban land ownership is questionable. The prohibition of dealings in Malay Reservation by non-Malays effectively created a category of agricultural land different from non-Reservation holdings in terms of the commercial value of the holdings. The insulation of Malay Reservation from non-Malay influence and dealings debarred the Malay owners from mortgaging their land to non-Malay moneylenders.